EXPLORATION OF THE INFLUENCE OF SOFT SKILLS ON CAREER EFFICACY OF SMK STUDENTS - Farida Aryani; Muhammad Rais; Hamdan Arfandi (JURNAL NALAR PENDIDIKAN, 2023)
This study aims to measure the influence of vocational students' soft skills on their career efficacy. This study uses a correlational quantitative method using mediation analysis on the JASP statistical application. The sample in this study consisted of 200 students using purposive sampling technique as many as 200 generation Z students who are vocational students were selected as respondents through several characteristics: 1) representing certain scientific fields / school majors; 2) the specified schools are spread throughout the South Sulawesi region; 3) the school is standardized on the Indonesian National Work Competency Standards. The data collection technique used a questionnaire adapted using Confirmatory Factor Analysis (CFA) test. The findings indicate that there is a significant influence between learners' soft skills on their career decisions. Learners who have or hone their soft skills will more easily direct themselves towards career decisions with confidence. Soft skills will also help vocational students to achieve more brilliantly in school to prepare for future careers. This study provides a conclusion that if the soft skills of vocational students are honed since the school period, it will affect career self-efficacy.